Suspected Central Nervous System Infections in HIV-Infected Adults - Sheybani, Fereshte; van de Beek, Diederik; Brouwer, Matthijs C. (Frontiers in Neurology, 2021)
Objectives: To study the differential diagnosis of HIV-infected patients with suspected central nervous system (CNS) infections and the association of CD4 counts with the final diagnosis. Methods: We analyzed HIV-infected patients from a prospective cohort study on the diagnostic accuracy of clinical and laboratory characteristics in adults with suspected CNS infections in an academic hospital in Amsterdam, the Netherlands, who underwent cerebrospinal fluid (CSF) examination. Results: Thirty-four (9.4%) out of 363 patients with suspected CNS infections were HIV-positive of whom 18 (53%) were diagnosed to have CNS infection, with median CD4 counts of 255 cells/μl. The spectrum of CNS infections consisted of progressive multifocal leukoencephalopathy in three patients (17%); cryptococcal meningoencephalitis, toxoplasma encephalitis, angiostrongylus eosinophilic meningitis, and HIV encephalitis each in two (11%); and cytomegalovirus encephalitis, neurosyphilis, tuberculous meningoencephalitis, histoplasma encephalitis, and varicella-zoster virus meningitis each in one (6%). Clinical characteristics and blood parameters did not differ between HIV-infected patients with CNS infections and other diagnoses. The best predictor for CNS infections was the CSF leukocyte count (AUC = 0.77, 95 CI% 0.61–0.94). The diagnosis of CNS infection was not associated with the CD4 count (median 205 vs. 370, p = 0.21). Two patients (11%) with CNS infections died and two (11%) had neurological sequelae. Conclusions: Half of the patients with suspected CNS infections are diagnosed with a CNS infection, and this was not related to CD4 counts. The best predictor for CNS infections was the CSF leukocyte count.